2015
DOI: 10.18632/aging.100833
|View full text |Cite
|
Sign up to set email alerts
|

Excess body weight increases the burden of age-associated chronic diseases and their associated health care expenditures

Abstract: Aging and excessive adiposity are both associated with an increased risk of developing multiple chronic diseases, which drive ever increasing health costs. The main aim of this study was to determine the net (non‐estimated) health costs of excessive adiposity and associated age‐related chronic diseases. We used a prevalence‐based approach that combines accurate data from the Health Search CSD‐LPD, an observational dataset with patient records collected by Italian general practitioners and up‐to‐date health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…Two further studies were identified and included following review of the reference lists of included articles. In total, 75 studies were included in the systematic review .…”
Section: Resultssupporting
confidence: 54%
“…Two further studies were identified and included following review of the reference lists of included articles. In total, 75 studies were included in the systematic review .…”
Section: Resultssupporting
confidence: 54%
“…23 A similar pattern has been observed in developed nations. 24,25 Our findings also point out that primary care services have strategic relevance regarding preventive actions aimed towards controlling obesity and its future complications.…”
Section: Discussionmentioning
confidence: 63%
“…In addition to documented co-morbidities, studies have also demonstrated that BMI is directly associated with healthcare cost [11,12]. A study by Li et al [11] (2015) assessed the economic burden of 21 obesityrelated disorders among 56,895 subjects and found that the costs associated with one prevalent obesity related condition (ORC), when all other ORCs were adjusted for, ranged from $120 (for angina) to $1665 (for pulmonary embolism) per person per year.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Li et al [11] (2015) assessed the economic burden of 21 obesityrelated disorders among 56,895 subjects and found that the costs associated with one prevalent obesity related condition (ORC), when all other ORCs were adjusted for, ranged from $120 (for angina) to $1665 (for pulmonary embolism) per person per year. In addition, a study by Attella et al [12] evaluated net health costs (the sum of indirect and direct costs) among 557,145 individuals, based on seven obesityrelated chronic diseases across BMI groups, and demonstrated a J-shape association between BMI and net health costs. The magnitude of this healthcare cost and how co-morbidities distribute across the population with obesity is unknown.…”
Section: Introductionmentioning
confidence: 99%